63 documents the government doesn't want you to read - Ventura, Jesse; Russell, Dick (New York : Skyhorse Pub., 2011)
Analyzes a series of public domain documents which demonstrate how the government has misled the public, engaging in deception about the objectives and scope of some of its programs and perpetuating wasteful spending and harmful cover-ups.
Includes bibliographical references.
Keywords: Official secrets -- United States; Government information -- United States; Government information -- Access control -- United States; Conspiracies -- United States; Government publications -- United States; Conspiracies